Leave No Bodymind Behind: Sins Invalid’s Vision of Crip Sustainability - Muehlemann, Nina (Peripeti, 2022)
This article discusses how the work of US-collective Sins Invalid, particularly the 2021 documentary Loving with Three Hearts and 2020 performance piece We Love Like Barnacles, addresses the exclusion of disabled people, especially multiply marginalised disabled people, in discourses and practices that address ecological disaster. The article argues that the company positions ableism as a crucial part of said exclusion and with their work proposes a version of sustainability that is rooted in collective access and care.